Case report of a Japanese patient with chronic renal failure who developed SARS‐CoV‐2 in a hospital cluster during treatment for acute respiratory failure: An autopsy report. Issue 7 (11th July 2022) - Amari, Yoshifumi; Morimoto, Satoshi; Teranishi, Takashi; Ohata, Mai; Takeshita, Atsushi; Hirano, Hiroshi; Kobayashi, Hitoshi
Abstract: This article reports a clinical and histopathological perspective which noted not only COVID‐19 pneumonia but also exacerbation of chronic renal failure potentially caused by thrombus in the kidney, possibly COVID‐19‐related lesions. The accumulation of autopsy cases will elucidate the pathogenesis of COVID‐19 and aid in the development of effective therapeutics. Abstract : This article reports a clinical and histopathological perspective which noted not only COVID‐19 pneumonia but also exacerbation of chronic renal failure potentially caused by thrombus in the kidney, possibly COVID‐19‐related lesions.